「KOTO NI NARU」, 「KOTO NI SURU」 AS FUKUJUTSUGO IN JAPANESE SENTENCES - Nani (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
This study is focused on identifying the meaning of the phrases 「koto ni naru」and 「koto ni suru」 as fukujutsugo. The data used in this study are verbal sentences with a compound predicate 「koto ni naru」and 「koto ni suru」. Based on the results of the analysis, it was identified that the phrases 「koto ni naru」 and 「koto ni suru」denote the meaning of decision or kettei (決定). The phrase 「koto ni natte iru」 as a variant of 「koto ni naru」 has expanded its meaning, namely it has become a decision that has become a regulation. The sentence with the predicate 「koto ni naru」 is not a personal decision. On the other hand, a sentence with the predicate 「koto ni suru」 means that the decision that is at the core of the sentence is his own decision. In a sentence that seems to highlight its own decision, the predicate with the phrase 「koto ni suru」 can be substituted by 「koto ni naru」.